Strategy for Teacher Development to Support the Competency-Based Education Policy - Sucharitrak, Phornsak; Sucharitrak, Suphatra; Misuna, Supawadee; Sucharitrak, Crissinee (Saengtham College Journal, 2026)
The objectives of this research were: 1) to examine the current conditions, desirable conditions, needs, strengths, weaknesses, opportunities, and challenges of teacher development in response to Competency-Based Education policies; 2) to develop strategies for teacher development to support Competency-Based Education policies; and 3)to validate the appropriateness and feasibility of the developed strategies. The sample consisted of 181 schools under the Office of Ratchaburi Primary Educational Service Area, determined using Krejcie and Morgan’s sample size table. A stratified random sampling technique was employed, using the educational service areas as strata. Two respondents were selected from each school: one school administrator and one teacher, yielding a total of 362 participants. The research instruments included a conceptual framework assessment form, a structured interview form, and a five-point Likert scale questionnaire with a reliability coefficient of 0.89. Strategy development was conducted using the TOWS Matrix, along with an appropriateness and feasibility evaluation form. Data were analyzed using frequency, percentage, mean, and standard deviation, as well as the priority needs index technique and content analysis. The research findings revealed that The current state of teacher development for the implementation of Competency-Based Education policies was found to be at a high level overall, while the desirable state was at the highest level. The most critical need for teacher development in this context lies in competency-based instruction. The major strength of teacher development was identified in the area of competency-based assessment and evaluation, whereas the weakness was found in competency-based instruction. Opportunities for teacher development were associated with the economic context, while obstacles emerged from technological, social, political, and policy-related factors. The development of strategies for teacher enhancement to support Competency-Based Education policies yielded three main strategies, seven sub-strategies across seven domains, and twenty-two operational approaches. Specifically: (1) curriculum management strategy consisted of three sub-strategies and nine operational approaches; (2) competency-based instruction strategy comprised two sub-strategies and six operational approaches; and (3) competency-based assessment and evaluation strategy included two sub-strategies and seven operational approaches. Overall, the three main strategies—competency-based curriculum management, competency-based instruction, and competency-based assessment and evaluation—were considered highly appropriate and highly feasible for implementation.